2018
DOI: 10.1073/pnas.1808241115
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous rewards promote cooperation

Abstract: SignificanceAn important research area in the social and biological sciences is how endogenous sanctions can promote cooperation in social dilemma situations, particularly in a budget-balanced (no need for external financing) manner. Punishment has had some success in experimental studies, but has serious shortcomings: It is socially wasteful materially and also tends to induce poor social relations. Reward avoids those issues and reinforces the social fabric. Our mechanism achieves high contributions in a pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Since the entry fee in our model is compulsory, a subsequent question is whether real players will choose such an incentive institution. A recent experimental study indicated that approximately half of the subjects would like to pay 20% of their wealth for a reward mechanism before playing the PGG [61]. This finding suggests that the incentive institution we proposed could be sustainable.…”
Section: Discussionmentioning
confidence: 82%
“…Since the entry fee in our model is compulsory, a subsequent question is whether real players will choose such an incentive institution. A recent experimental study indicated that approximately half of the subjects would like to pay 20% of their wealth for a reward mechanism before playing the PGG [61]. This finding suggests that the incentive institution we proposed could be sustainable.…”
Section: Discussionmentioning
confidence: 82%
“…For example, the hydrogenation of CO 2 to formic acid is entropically disfavored (ΔH 0 = −31.2 kJ mol −1 and ΔG 0 = +32.9 kJ mol −1 at 25 °C and pH = 0), and common strategies to alleviate this thermodynamic hurdle require the use of a stoichiometric amount of a Brønsted base (for NH 3(aq) , ΔH 0 = −84.3 kJ mol −1 and ΔG 0 = −9.5 kJ mol −1 at 25 °C) or highly polar solvents such as dimethyl sulfoxide or water (in water, ΔG 0 = −4.0 kJ mol −1 at 25 °C). 22 While the state-of-the-art is still dominated by noble-metal-based catalysts, 23 iron-or copper-based catalysts have emerged as potent candidates to promote this reaction. 24 Even more challenging is the hydrogenation of CO 2 to methanol, which is a kinetically difficult yet slightly exergonic reaction (ΔG 0 = −17.3 kJ mol −1 at 25 °C and pH = 0).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this study, we revisit the literature on the interplay between cooperation and (peer) rewarding 17 28 . This literature explores whether individuals become more cooperative when others can compensate them for their cooperative behaviors.…”
Section: Discussionmentioning
confidence: 99%